Evaluasi Jabatan Berbasis Eckenrode System pada PT Perkebunan Nusantara VIII - Sabila Syahidah; Erlin Trisyulianti (Jurnal Manajemen dan Organisasi, 2020)
PT Perkebunan Nusantara VIII is a company which operate in the field of agribusiness and agro industry. Based on the result of employee satisfaction and engagement survey report, it was found that employee satisfaction with salaries and benefits was in the unsatisfied category. Thus, this study aims to design a job evaluation based on eckenrode system to create a compensation model that could support to increase internal equity in the company. Compensation is one of the motivations for employees to work. This is might help the company to improve overall company’s performance. Data analysis method used in this study is eckenrode system method. The result of the study was obtained 10 factors that were made as factors for job evaluation and used as the basis for providing compensation, based on the result the existing occupational clusters, it is appropriate if it is made into three grades with the highest point in head of the division and the lowest point in the position of staff. The design of job evaluation based on eckenrode system can be used to make a new compensation model. The design can be used to calculate job points in other divisions and job points that have been obtained can be used to calculate the amount of the new salary at the company.